If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3+10y=9y-7
We move all terms to the left:
-3+10y-(9y-7)=0
We get rid of parentheses
10y-9y+7-3=0
We add all the numbers together, and all the variables
y+4=0
We move all terms containing y to the left, all other terms to the right
y=-4
| 3+5x=14x | | 8a+12=12 | | 2(x+5)+4x=2x+14 | | (x+20)/(-3)=4 | | -8s+3=-8s-2 | | -5(z-7)-8=27 | | 2x+5/10=42/20 | | 11+5x=16+4x | | (-4x)=20 | | 2b+10=-3b | | 3x-3=9+3x | | 5d=4=2d+6 | | Y=2x^2+11x-13 | | (2/3)(x+2)=20 | | 4(x+5)=4x5x | | 0=-8q+8q | | 5t^2+1785t-18900=0 | | 160+.50x=80+.90x | | 5t^2+1785-18900=0 | | -10+3j=3j-10 | | 4y+7-y=2+2y-5= | | -3/5g-1/3=-10/3 | | 3y^2-13y+9=0 | | 0=7w-7w | | √3x-6=-3 | | 4+2x=12+x | | x/3+8=-7 | | 5x+8-x=3+3x+8 | | 5(p+6)=3p+5 | | 2z-6=(z-1)÷2 | | -4.x=20 | | -9b-2=-10b |